Unknowability in Mathematics, Biology, and Physics. - Chaitin, Gregory J. (Social Research)
The article focuses on mathematical field dealing with unknowability is algorithmic information theory and halting probability Omega, which is defined as the probability that a self-contained computer program chosen at random will eventually halt. It mentions random mutations and natural selection are enough to account for the richness and diversity of biosphere. It also mentions developed field called systems biology that deals with computer simulations of complex biological systems. It discusses impossibility of a fundamental mathematical theory dealing with the effect of random mutations on natural software.